Menopausal hormone therapy - Taylor, Hugh (Henry Stewart Talks, 2007)
Menopause health risks, Hormone therapy in perspective, Reasons for continuing or initiating ERT/HRT, HRT benefits, Women's health initiative (WHI), Heart disease, Effect of Estrogen on risk of CHD, Breast cancer, Increased risk of breast cancer detection is not the same as breast cancer mortality or causality, The WHI did not consider disease latency, Low doses are recommended, Women's HOPE study